Comparing the effect of bio and organic fertilizers on some growth factors and yield of broad bean - AL-Kinany, Fadhel Safe Johe (Journal of Kerbala for Agricultural Sciences, 2016)
Field experiment was conducted in Hatamia / Balad ( 2014 ) using C.R.D design with three treatment to investigate and comparing the effect of biofertiizer of Rhizobium leguminosarum and organic manure (sheep res) with the recommended chemical fertilization on some growth factors and yield of broad bean. Results showed that significant differences among organic residues and biofertiizer with the reommanded chemical fertilizer for all studied parameters. Treatment of biofertiizers was the best on plant height 50.4 cm , number of branches 13.6/ pant , dry weight 16.98 gm , chlorophyll content 54.1mg.g-1 , protein percentage 26.39%, weight of 100 grains 195.46 gm , and total yield 1848.41 kg.ha-1 compared with reommanded chemical fertilizer addition , that gave lowest means in the studied parameters respectely ( 41.7 cm, 10.2 /plant, 11.97 gm, 51.6 mg.g-1, 24.13% , 162.27 gm, and 1684.93 kg.ha-1 ). This studying showed that we can use Bacteria Rhizobium leguminosarum as a biofertilizer with broad bean to improve growth an productivity.it can be retained 60 – 70 % from nitrogen fertilizer.